Динамический хаос в социуме как среда социальной самоорганизации - Добронравова, И.; Финкель, Л. (Социология: теория, методы, маркетинг, 2005)
Synergetic strategy of human actions for favorable choice of social selforganization presuggests the understanding of what kind of chaos presents in selforganizing medium. The article offers to consider the medium of political selforganization in Ukraine as dynamic, but not statistic chaos. This consideration is based on synergetic interpretation of visualized structures, obtained due to mathematical processing of data of elections to Verhovna Rada of Ukraine in 1998 and 2002.